Dwelling space in eastern Asia - Zgusta, Richard (Ōsaka Gaikokugo Daigaku Gakujutsu Shuppan Iinkai, 1991)
Evolution of space use in the Japanese house, dwellings of mainly insular Southeast Asia that tend to spatially favor the female element,The quadripartite pattern in space use in the Japanese rural dwelling.